2023
DOI: 10.1111/jfs.13081
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of antibacterial packaging film based on poly (vinyl alcohol)/agarose enriched with cinnamon oil

Thuong Thi Nguyen,
Bao‐Tran Tran Pham,
Dai Van Nguyen
et al.

Abstract: The antibacterial packaging films were produced from poly (vinyl alcohol) (PVOH), agarose, and cinnamon (Cinnamon cassia) oil (CO). The mechanical, antibacterial, water‐ and UV‐barrier properties of the resulting films were fully characterized. Our findings revealed that increasing amount of CO slightly affected the color of resulting film, while the dispersion of CO in polymeric matrix was influenced by CO concentration. UV‐barrier property of PVOH/agarose was enhanced by adding a small amount of CO. Tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…The WS of composite films first increases then decreases with the addition of LCEO, with the lowest WS occurring at the lowest WVP [30]. This result is generally consistent with the study of Nguyen et al [31], who reported that with the increase in essential oil content, the fracture elongation and water vapor transmittance of the film decreased. The main reason for this phenomenon is that the incompatibility between hydrophobic essential oil and the hydrophilic polymer (chitosan and starch) reduces the uniformity of the film structure, which is also the main reason for the decrease in TS.…”
Section: Physical and Mechanical Properties Of Filmssupporting
confidence: 90%
“…The WS of composite films first increases then decreases with the addition of LCEO, with the lowest WS occurring at the lowest WVP [30]. This result is generally consistent with the study of Nguyen et al [31], who reported that with the increase in essential oil content, the fracture elongation and water vapor transmittance of the film decreased. The main reason for this phenomenon is that the incompatibility between hydrophobic essential oil and the hydrophilic polymer (chitosan and starch) reduces the uniformity of the film structure, which is also the main reason for the decrease in TS.…”
Section: Physical and Mechanical Properties Of Filmssupporting
confidence: 90%